Stakeholders’ Perspective on Building Integrated Social Protection System in Nepal - Rasaili, Prem Kumar (Journal of Social Protection, 2023)
Following the inception of federalist structure, the three tiers of government is providing more than 80 social protection programmes in Nepal. The main purpose of this study is to assess the extent of coordination and integration of various programmes and provisions related to social protection, and to put forward better ways of coordination among them. This study adopted mixed method and partially applied the coordination toolkit developed by United Nations Development Group (UNDG) and ISPA. The study draws on analysis of available research, and in-depth interviews with concerned stakeholders using semi-structured questionnaires. Findings show that the involvement of multiple mechanisms and agencies for managing social protection schemes have created fragmentation, duplication, inefficiency, and ineffectiveness despite the fact that there is programme level vertical coordination within a single programme in some social protection schemes. There are a severe lack of horizontal coordination at the policy and operational level among programmes and mechanisms related to social protection. Implementation of international obligations, designing national policies and legal frameworks, establishing institutions, provisioning sustained funding mechanisms, generating political willpower, and using Integrated Management Information Systems (IMIS) are some strategies that can contribute to integration of the programmes. Moreover, it is very important to establish a single mechanism for coordinating the fragmented social protection activities for its sustainable implementation.